De novo transcriptome analyses of host-fungal interactions in oil palm (Elaeis guineensis Jacq.) - Ho, Chai Ling; Tan, Yung Chie; Yeoh, Keat Ai; Ghazali, Ahmad Kamal; Yee, Wai Yan; Hoh, Chee Choong (BioMed Central, 2016)
Background: Basal stem rot (BSR) is a fungal disease in oil palm (Elaeis guineensis Jacq.) which is caused by hemibiotrophic white rot fungi belonging to the Ganoderma genus. Molecular responses of oil palm to these pathogens are not well known although this information is crucial to strategize effective measures to eradicate BSR. In order to elucidate the molecular interactions between oil palm and G. boninense and its biocontrol fungus Trichoderma harzianum, we compared the root transcriptomes of untreated oil palm seedlings with those inoculated with G. boninense and T. harzianum, respectively. Results: Differential gene expression analyses revealed that jasmonate (JA) and salicylate (SA) may act in an antagonistic manner in affecting the hormone biosynthesis, signaling, and downstream defense responses in G. boninense-treated oil palm roots. In addition, G. boninense may compete with the host to control disease symptom through the transcriptional regulation of ethylene (ET) biosynthesis, reactive oxygen species (ROS) production and scavenging. The strengthening of host cell walls and production of pathogenesis-related proteins as well as antifungal secondary metabolites in host plants, are among the important defense mechanisms deployed by oil palm against G. boninense. Meanwhile, endophytic T. harzianum was shown to improve the of nutrition status and nutrient transportation in host plants. Conclusion: The findings of this analysis have enhanced our understanding on the molecular interactions of G. boninense and oil palm, and also the biocontrol mechanisms involving T. harzianum, thus contributing to future formulations of better strategies for prevention and treatment of BSR.